Assessment of the impacts and technicalities of gasification of municipal solid waste technology in UP Diliman - Laroza, Fiehl Amor R.
Waste-to-Energy (WtE) technology, particularly gasification, has a potential to be an alternative municipal solid waste (MSW) management method. As an emerging technology with several environmental impacts and economic returns, there is a need to study the impacts of gasification of MSW in UP Diliman as well as the technicalities involved prior to and during the operation of the gasification plant. The researcher gathered the necessary information by reviewing related literatures and studies and by conducting interviews with key experts. According to the UP Office of the Campus Architect, about 500 square meter land area located inside the university premises is available and is then identified as the prospective site of the WtE facility for this study. Several impacts on different aspects: environmental, social, economic, and health and safety, were identified in this study through the use of a comprehensive environmental impact checklist. Furthermore, strategies including mitigation measures were recommended in this study to lessen the negative impacts of the gasification plant in UPD. Based on the economic analysis done, a 200 kW gasification plant is projected to an economic return of P68,348,196.71 through Net Present Value analysis. Lastly, with the assumption of fully utilizing the campus own solid waste generation will reduce methane gas emission by 313,344 kg in 20 years.